(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Background: Microalbuminuria (MA) is the earliest clinical hallmark of diabetic nephropathy at which appropriate intervention can retard or reverse the progression of the disease. This aspect is not widely studied in young diabetic subjects of Bangladesh. Objectives: To determine the frequency of diabetic nephropathy (DN) in young diabetic patients and to identify the risk factors associated with it. Methods: This cross-sectional study included 88 participants [age: 26.19±3.33 years; body mass index (BMI, kg/m2): 25.42±5.39; mean±SD] with early-onset diabetes who were <30 years of age from the Department of Endocrinology, Bangladesh Medical University (BMU). The albumin-creatinine ratio (ACR) was estimated by immunoturbidometric assay. MA and macroalbuminuria were diagnosed if ACR was 30-300 mg/g of creatinine and >300 mg/g of creatinine, respectively. The estimated glomerular filtration rate (eGFR) was estimated by the CKD-EPI equation. Anthropometric measurements, as well as creatinine, were estimated along with fasting plasma glucose (FPG), postprandial plasma glucose (PPG), glycated hemoglobin (HbA1c), and lipid profile. Results: The frequency of diabetic nephropathy was 38.7%, with 30.7% having MA and 8% having macroalbuminuria, and only 2.2% of patients had eGFR <60ml/min/1.73 m2. There was a significantly higher frequency of MA with longer diabetes duration (p=0.010), higher FPG (p=0.045), higher HbA1c (p=0.025), and hypertriglyceridemia (p=0.009). No significant association between MA and blood pressure, BMI, or waist circumference was found. Logistic regression analysis showed that diabetes duration (p=0.008) and triglycerides (p=0.044) were independent predictors of albuminuria. Conclusions: The results of the study suggest a high frequency of diabetic nephropathy in young subjects. Longer duration of diabetes, hyperglycemia, and hypertriglyceridemia were important risk factors for nephropathy. So, the consequences of diabetes in the younger age group should not be overlooked. [J Assoc Clin Endocrinol Diabetol Bangladesh, July 2026; 5 (2): 89844]